Comparison of Sexual Hormone Secretion, Executive Brain Functions, and Changes in General Health in Women with and without Premenstrual Syndrome - Ramezani, Maryam; Mohammadi, Akbar (Psychology of Woman Journal, 2024)
Objective: This study aimed to compare the secretion of sexual hormones, executive brain functions, and changes in general health in women with and without premenstrual syndrome (PMS).Methods and Materials: The research design was a causal-comparative method. The statistical population included all women who visited the health center in Zanjan in 2023. The sample consisted of 200 women with and without PMS, selected using purposive convenience sampling. The instruments used in this research included blood tests, a PMS assessment questionnaire, the Wisconsin Card Sorting Test for assessing executive brain functions, and a general health questionnaire. Data analysis was performed using independent t-tests and multivariate analysis of variance (MANOVA).Findings: The findings indicated that the normal group had higher executive brain functions compared to those with PMS. Additionally, the general health of women with PMS was lower than that of the normal group. However, both groups exhibited the same level of progesterone hormone secretion, with no difference in the amount of progesterone secretion.Conclusion: The study found that women with premenstrual syndrome (PMS) exhibited lower executive brain functions and general health compared to women without PMS. No significant differences were observed in estrogen and progesterone secretion levels between the two groups. These findings suggest that PMS negatively impacts cognitive functions and general health, highlighting the need for targeted interventions to improve the quality of life for affected women.